Metal rules the globe : heavy metal music around the world - Wallach, Jeremy; Berger, Harris M., 1966-; Greene, Paul D. (Duke University Press, 2011)
This collection brings together cultural studies and pop music accounts of metal around the world, including Indonesia, Malaysia, Singapore, Nepal, Brazil, Malta, Slovenia, China, Japan, Norway, Israel, and Easter Island. The volume is divided into sections covering the broader topics of gender, nation, racism, the music industry, and global and local perspectives.